Lived Experience and Family Engagement in Mental Health and Substance use Health Research: Case Profiles of Five Studies - Lisa D. Hawke; Lena Quilty; Branka Agic; Darren B. Courtney; Gray Liddell; Etienne Sibille; Sheila Jennings; Joshua Orson; Holly Harris; Shelby McKee; Cara Sullivan; Sophie Soklaridis; et al. (Health Expectations)
ABSTRACT Introduction People with lived and living experience (PWLLE) and family members (F) can engage in mental health and substance use health research beyond participant roles, as advisors, co‐researchers, equal partners and research leads. However, implementing meaningful and effective engagement is complex. Methods This article profiles five research initiatives involving different lived experience engagement structures, situated in a single tertiary care teaching and research hospital. Results The profiled projects feature various study designs and stages, ranging from initial priority setting to implementation efforts. The levels of engagement range from consultation to PWLLE/F leadership. Across diverse populations, all embody high‐quality engagement and illustrate that PWLLE/F can have an important impact on a wide range of mental health and substance use health research. Conclusions Engagement can be implemented flexibly within a single research institution to meet a wide range of needs and preferences of researchers and PWLLE/F. Patient and Public Contribution Each of the research initiatives profiled was conducted with substantial lived experience engagement, as described herein. People with lived and living experience from each research initiative are also included in the authorship team and contributed to this manuscript.